Not enough : human rights in an unequal world - Moyn, Samuel (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2019)
The age of human rights has been kindest to the rich. As state violations of political rights garnered attention, a commitment to material equality disappeared and market fundamentalism emerged as the dominant economic force. Samuel Moyn asks why we chose not to challenge wealth and neglected the demands of a broader social and economic justice.--
Jacobin legacy: the origins of social justice -- National welfare and the universal declaration -- FDR's second bill -- Globalizing welfare after empire -- Basic needs and human rights -- Global ethics from equality to subsistence -- Human rights in the neoliberal maelstrom.
Includes bibliographical references and index.
GenED
Keywords: Human rights -- History; Equality -- History; Welfare economics -- History; Neoliberalism -- History